Design and development of a controller for switching solar based multiple pumps - Ahmed, Syeda Mahjabin; Akter, Tasnim (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.